Supercritical fluid extraction of Arbutus unedo distillate residues – Impact of process conditions on antiproliferative response of extracts. Issue 37 (April 2020) - Alexandre, A.M.R.C.; Serra, A.T.; Matias, A.A.; Duarte, C.M.M.; Bronze, M.R.
Graphical abstract: Highlights: Arbutus unedo distillate residues still have a panoply of bioactive compounds. Supercritical fluid extraction using carbon dioxide and ethanol proved to extract different classes of compounds. Pyrogallol and gallic acid within the extracts presented antiproliferative activity towards HT29 cells, without being cytotoxic. The use of 20% co-solvent and the highest conditions of pressure and temperature result in extracts with both high yields and lowest EC50. Residue should be taken into account in a biorefinery perspective. Abstract: The strawberry tree ( Arbutus unedo ) is an evergreen plant belonging to the Ericaceae family, an endemic specie of the Mediterranean. In Portugal it grows mostly wild and its fruits are mainly used to produce a distillated alcoholic beverage called "Aguardente de Medronho". From the process, a residue is obtained which is normally discarded, despite it may figure as biomass for valorization. This work intends to study different conditions of supercritical fluid extraction (SFE), using carbon dioxide as solvent and ethanol as co-solvent for the recovery of bioactive compounds from that residue. After a screening design of experiments varying pressure, temperature, co-solvent, flow rate and time of extraction, an optimization design of experiments (central composite design) was performed. Time (90 min) and flow rate (10 g/min) were established. Variables were pressure (100, 200 and 300 bar), temperature (35, 45 and 55 °C) and co-solvent concentration (0, 10 and 20 %). Extracts were analyzed by GC–MS and LC–MS/MS and cytotoxicity and antiproliferative effect of the extracts was evaluated in Caco2 and HT-29 cell models respectively. Chemical characterization showed an increase in phenolic compounds such as pyrogallol, gallic acid, catechol and protocatechuic acid amongst others, with the increase of the co-solvent. GC–MS analysis revealed a diversity of compounds from fatty acid esters, terpenes and small molecules with recognized bioactivity. The most promising extract was obtained using 300 bar and 55 °C and 20 % of co-solvent. Besides being the extract with the highest yield, it also presented the lowest EC50 (0.569 mg/mL) mainly due to the presence of phenolic compounds.